Tracking Economic and Financial Policies During COVID-19 : An Announcement-Level Database - Kirti, Divya; Liu, Yang.; Martinez Peria, Soledad; Mishra, Prachi.. (Washington, D.C. : International Monetary Fund, 2022)
We introduce a new comprehensive announcement-level database tracking the extraordinary fiscal, monetary, prudential, and other policies that countries adopted in response to Covid-19. The database provides detailed information, including sizes where available, for 28 granular policies adopted by 74 countries during 2020. About 5,500 policy measures were announced during this period. Importantly, the database is organized and presented in a format easy for researchers to use in empirical analyses. Announcements were highly correlated across the broad fiscal, monetary, and prudential categories and at more granular levels. Advanced economies (AEs) introduced larger fiscal measures than emerging and developing economies (EMDEs) and relied primarily on large unconventional monetary policies. Bank capital requirements were relaxed widely in both AEs and EMs, while relaxation of provisioning requirements was more common among EMs. Supervisory expectations and reporting requirements were widely relaxed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Central Banks and Their Policies; Depository Institutions; Fiscal Policy; Monetary Policy